Optimizing brackish water irrigation strategies: Promoting the ecological and economic benefits of salt wasteland utilization - Qiang Xu; Yibin Xu; Hanji Xia; Qian Zhang; Pengfei Li; Hongguang Liu; Mingsi Li; Ping Gong (Agricultural Water Management, 2025)
The depletion of freshwater resources and soil salinization caused by climate change and human activities significantly threatens to agricultural productivity in arid regions. The use of salt waste and brackish water for the production of Suaeda salsa vegetables and forage is a win-win strategy for agricultural ecology and economic benefits in arid areas. A field experiment was conducted over two consecutive years, using a complete combination design that included three irrigation water volumes and three irrigation water salinity levels. The volumes of irrigation water employed were 1840 (W1), 2950 (W2), and 3884 m3 ha–1 (W3). The irrigation water sources used were the Yerqiang River and groundwater, which were mixed at ratios of 100 %:0 %, 50 %:50 %, and 0 %:100 %. The corresponding salinity levels in the irrigation water were 2.12–4.30 (S1), 11.93–14.69 (S2), and 20.60–26.42 dS m–1 (S3), respectively, with a total of 9 treatments. The results revealed that when the irrigation water volume increased, the vegetable yield, forage yield, vegetable quality, forage quality, nitrogen content, irrigation water productivity, desalination capacity, and net profit of Suaeda salsa first increased but then decreased. With increasing irrigation water salinity, vegetable quality, forage quality, nitrogen content, and desalination capacity decreased, whereas vegetable yield, forage yield, irrigation water productivity, and net profit first increased but then decreased. Notably, W2S2 had the highest vegetable yield, forage yield, WPi, and net profit, whereas W2S1 had the highest vegetable quality, forage quality, nitrogen content, and desalination capacity. It is therefore necessary to consider the economic and ecological benefits of the development and utilization of salt wasteland through the implementation of multiobjective optimization. The optimal range of irrigation water volume was 3068.91–3585.74 m3 ha–1, and the salinity range was 9.04–10.70 dS m–1. This study provides a reference for optimizing brackish water irrigation strategies, enhancing the efficiency of water and soil resources in arid areas, and enhancing the ecological and economic benefits of saline wasteland utilization.